Walking the tightrope: ego support and exploration with a child with complex trauma. Issue 3 (2nd September 2021) - Bervoets, Eva; Meurs, Patrick; Luyten, Patrick; Tang, Eileen; Vliegen, Nicole
ABSTRACT: Children who have experienced complex trauma in early life often fail to develop robust ego functions, such as frustration tolerance and emotion regulation capacities. Often, impairments in these capacities persistently characterise these children's social and emotional development and, as such, prove extremely challenging to the adults who care for them. This paper aims to illustrate different ways in which therapists working with these children in psychodynamic therapy have to find a precarious balance between the need to support developing ego functions, and opportunities to conduct more exploratory work. This balance resembles walking a tightrope. We illustrate this 'balancing act' with case excerpts from the treatment of nine-year-old Laura, growing up in foster care after a range of complex traumatic experiences. This case study seeks to illustrate that psychotherapy with children who have a history of complex trauma may be most conducive to developmental recovery, if the therapist is able and willing to almost unabatingly walk the tightrope between ego-supportive and exploratory work with the child.